2009
DOI: 10.1103/physrevlett.102.033601
|View full text |Cite
|
Sign up to set email alerts
|

Spin Squeezing of a Cold Atomic Ensemble with the Nuclear Spin of One-Half

Abstract: To establish an applicable system for advanced quantum information processing between light and atoms, we have demonstrated the quantum non-demolition (QND) measurement with a collective spin of cold ytterbium atoms ( 171 Yb), and observed 1.8 +2.4 −1.5 dB spin squeezing. Since a 171 Yb atom has only a nuclear spin of 1/2 in the ground state, the system is the simplest spin ensemble and robust against decoherence. We used very short pulses with the width of 100 ns, so the interaction time became much shorter t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
148
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 27 publications
1
148
1
1
Order By: Relevance
“…It has been demonstrated that the TAT spin squeezing can be transformed from the OAT type by using repeated Rabi pulses [20]. Moreover, many other mechanisms are promising for producing SSSs [21,22,23,24,25,26]. The fact is that the SSSs is one type of quantum entangled states.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the TAT spin squeezing can be transformed from the OAT type by using repeated Rabi pulses [20]. Moreover, many other mechanisms are promising for producing SSSs [21,22,23,24,25,26]. The fact is that the SSSs is one type of quantum entangled states.…”
Section: Introductionmentioning
confidence: 99%
“…Such backaction evading techniques were first realized for the detection of optical quadratures [21][22][23] and have since been used for, e.g. precision measurement of atomic ensemble spin [24][25][26][27][28] and quantum non-demolition microwave photon counting [29]. In optomechanics, to perform a back-action evading measurement of the mechanical position, a time-dependent measurement scheme is required.…”
mentioning
confidence: 99%
“…Nonfluorescence based atom-counting in 87 Sr [28,29] and 171 Yb [33] have been performed using the dipole-allowed transition 1 S 0 to 1 P 1 and no optical cavity. Atomic proarXiv:1506.02297v1 [physics.atom-ph]…”
mentioning
confidence: 99%
“…Nonfluorescence based atom-counting in 87 Sr [28,29] and 171 Yb [33] have been performed using the dipole-allowed transition 1 S 0 to 1 P 1 and no optical cavity. Atomic pro-jection noise level sensitivity was achieved, but with the scattering of ∼ 100 photons per atom [28,29] and with uncharacterized scattering [33]. While [28,29] demonstrated that the atoms were retained in the lattice trap, the need to re-cool the atoms leads to additional stochastic losses [34].…”
mentioning
confidence: 99%